The Effect of Growth Regulators on Some Photosynthetic Traits and Maintenance of Cell Membrane Structure of Flag Leaf of Two Wheat Cultivars under Rainfed Conditions - Ali Rasaei; Saeid Jalali-Honarmand; Mohsen Saeidi; Mohammad-Eghbal Ghobadi (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
When the plant is exposed to abiotic stresses, the cell membrane is the first part of the cell to be affected by stress, and the relationships of the many of physiological and biochemical cell of the plant are disrupted. The effect of three growth hormones (3 indoleacetic acid [IAA], gibberellic acid [GA3] and 6 benzylaminopurine [6 BAP]) with a control (distilled water) was evaluated at booting stage of two wheat cultivars (Rijaw and Azar 2). A factorial experiment using a randomized complete block design (RCBD) with three replications was setup at Campus of Agriculture and Natural Resources, Razi University, Kermanshah, Iran in 2013-14 and 2014-15. Based on the results, the effect of different growth hormones on SPAD, relative water content, Fv/Fm, performance index, leaf cell membrane stability and photosynthetic rate of both cultivars were significant. Among growth hormones, foliar application of Cytokinin and Auxin had the greatest effect on the measured leaf traits and the lowest mean of the traits was obtained in non-spraying treatment (control). Between the two cultivars, Rijaw cultivar was superior to Azar-2. There was also a positive and significant correlation between cell membrane stability and photosynthesis rate, Fv/Fm and performance index. In general, in dryland conditions (water deficiency) with external application of cytokinin in booting stage in superior wheat cultivar (Rijaw) cell membrane stability, relative water content, photosynthetic rate and Fv/Fm were 16, 18, 38 and 45 percent higher than the control, respectively.